'An Image of Hope in a Week of Despair': Representations of Sam the Koala in the Australian Mainstream News Media. Issue 1 (May 2014) - Due, Clemence; Thompson, Kirrilly; Every, Danielle
Natural disasters are events with far-reaching humanitarian implications that frequently receive international attention through the use of an image that comes to represent the disaster in question. The most successful images often comprise 'identifiable' and therefore human victims. What is more unusual is for a single animal image to become representative of an entire disaster. This was the case with the 2009 Victorian bushfires in Australia, when the image of a firefighter offering a koala a drink gained international fame. Given that this image of 'Sam' the koala does not conform to traditional disaster imagery, we undertook a thematic analysis of mainstream news media representations of Sam in order to identify how she was represented by the media. In this article, we discuss these themes in relation to the 'identifiable victim', together with the implications of Sam's success in terms of disaster-relief campaigns.